The State of Records Management Practices in Public Offices: A Case of Kinondoni Municipal Council in Dar es Salaam, Tanzania - Rutta, Mwombeki; Ndenje-Sichalwe, Esther (University of Dar es Salaam Library Journal, 2022)
This study assessed the current state of records management practices at the Kinondoni Municipal Council (KMC) in Dar es Salaam, Tanzania for good service delivery. Specifically, the study examined the state of the existing records management programme and identified the challenges encountered in managing records. The study employed a mixed methods research design that had recourse to both quantitative and qualitative approaches for data collection and analysis. Its sample of 64 respondents was selected from a population of 124 respondents using purposive sampling for top management officials and records and simple random sampling for other KMC employees comprising action officers and Human Resources Officers (HROs). Triangulation of data collection methods was employed using questionnaires, interviews, observations and documentary review. The key findings show that the KMC lacked an effective records management programme to ensure effective records management practices. Records management programme lacks institutional legal and regulatory framework, hence the largely ineffective records management practices at the KMC. Inevitably, the council contended with several challenges including lack of security measures, and lack of skills and lack of guidance from the Records and Archives Management Department (RAMD). Thus, the study recommends that the KMC should improve its records management programme by establishing legal frameworks, training staff and prioritising the records management unit.